2021
DOI: 10.7759/cureus.18511
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Ipsilateral Femoral Neck and Shaft Fractures Treated With Proximal Femoral Nail Antirotation 2

Abstract: Ipsilateral femoral neck and shaft fractures are relatively rare fractures, which most commonly occur in young adults following high-energy trauma. In most cases of such fractures, neck fracture is undisplaced and often of basicervical type. Many treatment methods have been described, but there is still no generalized consensus on the same. Cephalomedullary nails are one of the preferred modalities of treatment. A cephalomedullary nail-like proximal femoral nail antirotation 2 (PFNA 2) of recent design is bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
(27 reference statements)
0
10
1
Order By: Relevance
“… Time to union PF (months) Time to union SF (months) Mean follow-up (range) Chaudhary et al (2021) [ 61 ] 2018–2020 7 (7) 5 (71%) 35 (27–45) 7 (100%) FN + TF N.A. 0 7 4.1 (3–6) 5.1 (3–11) 16.2 (10–22) Rana et al (2021) [ 62 ] 2018–2020 13 (13) 8 (62%) 38 (23–54) 13 (100%) FN N.A. 13 0 4.3 (N.A.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Time to union PF (months) Time to union SF (months) Mean follow-up (range) Chaudhary et al (2021) [ 61 ] 2018–2020 7 (7) 5 (71%) 35 (27–45) 7 (100%) FN + TF N.A. 0 7 4.1 (3–6) 5.1 (3–11) 16.2 (10–22) Rana et al (2021) [ 62 ] 2018–2020 13 (13) 8 (62%) 38 (23–54) 13 (100%) FN N.A. 13 0 4.3 (N.A.)…”
Section: Resultsmentioning
confidence: 99%
“…Only seven studies reported sufficient data concerning operation time and perioperative blood loss [ 19 , 28 , 49 , 54 , 59 , 61 , 62 ]. Table 2 shows the pooled analysis for operation time and perioperative blood loss for both treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors argue that in the FN-FD setting, the clear biomechanical advantages of nailing long bone fractures ( 49 ) are outweighed by the technical difficulties especially in accurately placing the proximal screws into the head and neck ( 36 ). Precise reduction and maintaining rotational stability of the head and neck fracture during nail placement is considered the priority in the treatment ( 48 ), but it is technically demanding ( 8 , 34 ). The nail insertion may displace an undisplaced fracture, potentially compromising its blood supply ( 8 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following the identification and development of the nail entry point at the tip of the greater trochanter and the insertion of the long guide wire to the centre of the distal femoral metaphysis, the medullary canal is slightly over-reamed (+2 mm of the nail diameter in a stepwise fashion with flexible reamers) to facilitate nail insertion without displacing the femoral neck fracture ( 34 , 35 ). The insertion of the nail is followed by the two proximal (cephalomedullary screws) and subsequent distal locking screws ( 36 ).…”
Section: Managementmentioning
confidence: 99%
“…Use of cephalomedullary nails (CMNs) in these injuries has begun to emerge with promising preliminary data. 33,34 However, more data are needed before making any strong recommendations on use of CMNs for high-energy femoral neck fractures. Recently, the use of fibular struts to augment cannulated screw constructs has been investigated; however, Kumar et al 35 were unable to show any clinical differences associated with this fibular strut augmentation.…”
Section: Fixation Techniquesmentioning
confidence: 99%